Fossilized Errors of English Morphosyntax Committed by English Graduate Students in Thesis Seminar Presentation at Universitas Negeri Padang - Sri Muliati; Hermawati Syarif; Jufrizal Jufrizal (English Language Teaching and Research, 2017)
The paper aims at discussing the kinds of fossilized errors of morphosyntax which occur in students’ oral communication and to find out the most possible factors causing those errors. There were 10 English graduate students who held thesis seminar as the subject of the study. The data were collected from the students’ utterances during their thesis seminar presentation which were recorded and transcribed then analyzed based on the indicators predetermined. To see the truthfulness of the data, the interview was done, especially to see the factors causing fossilized errors. The results show that 8 out of 10 subjects committed fossilized error and the frequent fossilized errors were manifested in using number marking (taking singular for plural marking) in noun/noun phrase category and substitution of the simple present for the simple past tense, the use of voice, agreement and nominalization. These fossilized errors were due to the Indonesian language interference, pedagogic intervention, and lack of opportunity to use English. Based on the result, it is recommended that the lecturers pay serious attention to the language usage in preparing effective writing instructional design. Key words: Error analysis, fossilized error, morphosyntax, interference, speaking.